Statistical Learning as a Tool for Rehabilitation in Spatial Neglect - Shaqiri, Albulena; Anderson, Britt; Danckert, James (Frontiers in Human Neuroscience, 2013)
We propose that neglect includes a disorder of representational updating. Representational updating refers to our ability to build mental models and adapt those models to changing experience. This updating ability depends on the processes of priming, working memory, and statistical learning. These processes in turn interact with our capabilities for sustained attention and precise temporal processing. We review evidence showing that all these non-spatial abilities are impaired in neglect, and we discuss how recognition of such deficits can lead to novel approaches for rehabilitating neglect.